2021
DOI: 10.1016/j.scs.2021.103410
|View full text |Cite
|
Sign up to set email alerts
|

An evaluative model for assessing pandemic resilience at the neighborhood level: The case of Tehran

Abstract: The spread of the COVID-19 virus, which has caused abundant mortalities in human settlements, has drawn the attention of urban planners and policy-makers to the necessity of improving resilience to future pandemics. In this study, a set of indicators related to pandemic resilience were identified and used to develop a composite multi-dimensional pandemic resilience index for Tehran's neighborhoods. The physical, infrastructural, socio-economic, and environmental dimensions of pandemic resilience were defined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The findings of this study are consistent with the findings of [ 92 , 93 ]; and [ 94 ] in Iran and Tehran. They also found that neighborhoods with better economic and social conditions and more active economic and commercial sectors have a higher incidence.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study are consistent with the findings of [ 92 , 93 ]; and [ 94 ] in Iran and Tehran. They also found that neighborhoods with better economic and social conditions and more active economic and commercial sectors have a higher incidence.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, environmental features play an essential role in community mitigation and absorption capacity [ 59 , 70 ]. In addition, demographic resilience can influentially reduce community vulnerability to pandemics by mitigating the infection rate, minimizing death cases, and facilitating the process of recovery and inhibition of disease [ 36 , 71 ]. These dimensions are further discussed in the following sections.…”
Section: Resultsmentioning
confidence: 99%
“…While they have explored different capitals, their study falls short of exploring how each capital and capacity factors could contribute to community pandemic resilience. To the same, Lak et al [ 36 ] have evaluated the pandemic resilience of the Tehran neighborhoods considering physical, demographic, environmental, infrastructural, economic, and social dimensions. This study did not include the institutional aspect of community pandemic resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assist people in healthy travel planning, it is necessary to be able to predict and identify the spatiotemporal risk hotspots of COVID-19 ( Ghosh and Cartone, 2020 ; Sharifi and Khavarian-Garmsir, 2020 ). Since the outbreak of COVID-19, a series of studies on predicting and identifying risk hotspots have emerged ( Das et al, 2021 ; Guo et al, 2021 ; Islam et al, 2021 ; Lak et al, 2021 ; Sannigrahi et al, 2020 ). For example, Jia et al used a spatiotemporal risk source model to identify the areas within high transmission risk and statistically derive the geographical spread and growth pattern of COVID-19 in China ( Jia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%